2022
DOI: 10.1111/dom.14773
|View full text |Cite
|
Sign up to set email alerts
|

What is the value of faster acting prandial insulin? Focus on ultra rapid lispro

Abstract: Rapid‐acting insulins (RAIs) have been instrumental in the management of diabetes because of their improved postprandial glucose (PPG) control compared with regular human insulin. However, their absorption rate and time action following subcutaneous administration still falls short of the normal physiological response to meal consumption, increasing the risk of early postmeal hyperglycaemia and late postmeal hypoglycaemia. Increased demand for faster acting insulins, which can quickly control PPG excursions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…One might argue that accelerating absorption via an IVM is an unnecessary redundancy now that ultra-rapid acting insulins are available. However, the very rapid peak plasma insulin concentrations achieved with regular insulin via IVM more closely mimic the normal human pancreas and are likely superior to even ultra-rapid acting insulins injected SC [16, 49, 50]. The insulin kinetic curves (Fig 2 B, D) are compatible with an “inject-eat continuum” strategy: this would, first, synchronize the insulin peak with the prandial requirement; and second, avoid the pitfalls of inopportune delays of a meal by simply postponing the injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One might argue that accelerating absorption via an IVM is an unnecessary redundancy now that ultra-rapid acting insulins are available. However, the very rapid peak plasma insulin concentrations achieved with regular insulin via IVM more closely mimic the normal human pancreas and are likely superior to even ultra-rapid acting insulins injected SC [16, 49, 50]. The insulin kinetic curves (Fig 2 B, D) are compatible with an “inject-eat continuum” strategy: this would, first, synchronize the insulin peak with the prandial requirement; and second, avoid the pitfalls of inopportune delays of a meal by simply postponing the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Another argument sometimes made is that rapid uptake of insulin confers more risk than benefit, for example, by triggering hypoglycemic episodes. However, the clinical safety and efficacy, especially in post-prandial control, of ultra-rapid acting insulins is now supported by many studies [15, 16, 52, 53]. The factitious “too rapid” assertion also deflects the many advances in continuous glucose monitoring (CGM) devices, insulin dosage-predicting algorithms, precision-dosing insulin pumps, open and closed loop systems, and the “artificial pancreas” (AP) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Wegen des schnelleren Wirkungseintritts ist es noch besser steuerbar, insbesondere bei Menschen mit Typ-1-Diabetes und solchen mit einer Insulinpumpentherapie [294]. Die Insulinwirkung von ultraschnell wirkendem Insulin lispro (URLI = Ultra Rapid Lispro Insulin) führte zu einer deutlich besseren postprandialen Glukosekontrolle, ganz gleich ob dieses Insulin vor, während oder nach der Mahlzeit (-15 bis + 15 Minuten) s. c. gespritzt wurde [296]. Die postprandialen Glukose-Exkursionen über 5 Stunden wurden mit URLI um 29 % bis 105 % gesenkt.…”
Section: Schnellwirkende Insulin-analogaunclassified
“…Ultra rapid lispro (URLi; Lyumjev ® ) is a formulation of insulin lispro with a faster onset and shorter duration of action compared to Lispro (Humalog ® ) and was developed to more closely match physiological insulin secretion and improve PPG control [ 12 ]. URLi has demonstrated non-inferiority to Lispro in HbA1c change from baseline after 26 weeks in people with type 1 diabetes (T1D) (PRONTO-T1D) and T2D (PRONTO-T2D) while providing superior PPG control when dosed at mealtime [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that introducing a rapid-acting prandial insulin as part of a basal-bolus multiple daily injection (MDI) regimen is more effective at managing PPG than a basal-only regimen [9][10][11]. Nevertheless, rapid-acting insulins still may not have fast enough onset to match carbohydrate absorption resulting in inadequate control of PPG [12].…”
Section: Introductionmentioning
confidence: 99%